Superior Effects of High-Intensity Interval vs. Moderate-Intensity Continuous Training on Endothelial Function and Cardiorespiratory Fitness in Patients With Type 1 Diabetes: A Randomized Controlled Trial - Boff, Winston; da Silva, Antonio M.; Farinha, Juliano B.; Rodrigues-Krause, Josianne; Reischak-Oliveira, Alvaro; Tschiedel, Balduino; Puñales, Marcia; Bertoluci, Marcello C. (Frontiers in Physiology, 2019)
To compare the effect of high-intensity interval training (HIIT) with moderate-intensity continuous training (MCT) on endothelial function, oxidative stress and clinical fitness in patients with type 1 diabetes. Thirty-six type 1 diabetic patients (mean age 23.5±6 years) were randomized into 3 groups: HIIT, MCT, and a non-exercising group (CON). Exercise was performed in a stationary cycle ergometers during 40 min, 3 times/week, for 8 weeks at 50-85% maximal heart rate (HRmax) in HIIT and 50% HRmax in MCT. Endothelial function was measured by flow-mediated dilation (endothelium-dependent vasodilation [EDVD]), and smooth-muscle function by nitroglycerin-mediated dilation (endothelium-independent vasodilation [EIVD]). Peak oxygen consumption (VO2peak) and oxidative stress markers were determined before and after training. Endothelial dysfunction was defined as an increase <8% in vascular diameter after cuff release. The trial is registered at ClinicalTrials.gov, identifier: NCT03451201. Twenty-seven patients completed the 8-week protocol, 9 in each group (3 random dropouts per group). Mean baseline EDVD was similar in all groups. After training, mean absolute EDVD response improved from baseline in HIIT: +5.5±5.4%, (P=0.0059), but remained unchanged in MCT: 0.2±4.1% (P=0.8593) and in CON: -2.6±6.4% (P=0.2635). EDVD increase was greater in HIIT vs. MCT (P=0.0074) and CON (P=0.0042) (ANOVA with Bonferroni). Baseline VO2peak was similar in all groups (P=0.96). VO2peak increased 17.6% from baseline after HIIT (P=0.0001), but only 3% after MCT (P=0.055); no change was detected in CON (P=0.63). EIVD was unchanged in all groups (P=0.18). Glycemic control was similar in all groups. In patients with type 1 diabetes without microvascular complications, 8-week HIIT produced greater improvement in endothelial function and physical fitness than MCT at a similar glycemic control. Keywords: high-intensity interval training; endothelium; diabetes mellitus, type 1